Evidence-Based Practice in Physiotherapy: Challenges, Clinical Reasoning, and Strategic Pathways in Developing Contexts - Rijal, Rijal (Physiotherapy, Exercise, and Rehabilitation Sciences Journal, 2026)
Evidence-Based Practice (EBP) has become a fundamental paradigm in modern physiotherapy, highlighting the integration of the best available research evidence with clinicians’ professional expertise and patient values to guide informed clinical decision-making. Since its formal integration into the health sciences, Evidence-Based Practice (EBP) has been extensively advocated as a means to improve patient outcomes, enhance professional accountability, and optimize the efficiency of healthcare resource utilization (1). Although these expected advantages exist, the integration of EBP from theoretical models into everyday physiotherapy practice remains uneven and difficult within the industry. These difficulties are especially evident in low- and middle-income nations, such as Indonesia, where challenges like restricted access to high-quality evidence, differences in educational training, and systemic limitations continue to influence clinical practices (2). In this scenario, analyses based on perspectives are crucial to go beyond standard descriptions of EBP and to critically assess how evidence is interpreted, negotiated, and implemented in actual physiotherapy settings (3). This article, therefore, delves into the essential conceptual foundations, clinical reasoning processes, and strategic pathways associated with EBP in physiotherapy. It draws on both educational and clinical experiences to underscore opportunities for more contextually responsive and sustainable implementation